Instruction Program for Nurses Knowledge about Applying the Communication Strategies (SBAR) in Critical Care Units - Haneen Qahtan Abadi; Huda Baker Hassan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Effective communication can improve patient care and safety by ensuring complete andcorrect information transmission and preventing misrepresentation and misinterpretation of patientcentereddata. Situation, Background, Assessment and Recommendation (SBAR) is the one of the mosteffective communication strategies that used in transmitted the clinical information between the healthprofessionals.Objectives of the Study: Present study aims to determine the effectiveness of Instruction program onnurses’ knowledge regarding communication strategy (SBAR) and find out the association betweenthe effectiveness of instruction program and nurses’ level of education, year of experiences, year ofexperiences in critical units and training course.Methodology: A pre-experimental study design was carry out in the critical care units of Imam Al-Hussein Medical City at Holy Karbala City between the periods 17th of September 2020 to 25th of May2021. A non-probability (purposive) sample of (25) nurses were selected based on the study criteria.Results: The results of the study indicated that there were high statistically differences between thepre and post-test of the instruction program related to the communication strategy. The study found ahigh statistically significant relationship between the effectiveness of the instruction program relatedto the communication strategy, educational level, training courses for nursing documentation, years ofexperience in nursing, and years of experience for nurses in the critical care units.Conclusion: The study concluded that the instruction program had a positive eefect on nurses’knowledge concerning communication strategy (SBAR). Recommendations: Testing the current program on a wide group of health-care providers in hospitals.